If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15a + 25b = 0 Solving 15a + 25b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-25b' to each side of the equation. 15a + 25b + -25b = 0 + -25b Combine like terms: 25b + -25b = 0 15a + 0 = 0 + -25b 15a = 0 + -25b Remove the zero: 15a = -25b Divide each side by '15'. a = -1.666666667b Simplifying a = -1.666666667b
| 101+80+65+y=(4-2)180 | | 1-5n+1+3n= | | 101+80+75+y=(4-2)180 | | 9a+6ab+39c+6ab+-26b+13c= | | 10x-1=328 | | 15v-8v=28 | | 15v-18v=28 | | 74+89+98+y=(4-2)180 | | 13ab+-7b+17a+2ab+b= | | 3(4x+9)-6x=0 | | 42=2w+16 | | 3X=1-y-4z | | 2x+4x+6x+8x=360 | | 72+100+83+y=(4-2)180 | | 2ab+-17b+13ab+-7b= | | cos(5x)+cos(7x)=cosx | | 6+-2c+3=7+c | | y-1=-1(x+3) | | a-b=5b | | 3x-3=7x-1 | | 25x^2-45-10=0 | | 6x^7=11x^6 | | 13c+4ab-9b+2ab+-17b= | | 6+2c+3=7+c | | 13k^2+26k+13= | | X(x-2a)+a^2+1=0 | | w^6+8w^3+7=0 | | d^6+2d^3-80=0 | | 9a+26c+2ab+13c+4ab-9b= | | -14y=7x+1 | | 12a^3b^2-27ab^2=0 | | 4(1-x)+7x=4 |